Analisis Data Produksi Ikan Konsumsi Menggunakan Uji Friedman - Emy Natun Na'imah; Siti alfiatur Rohmaniah (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
Agriculture in Lamongan district is known as minipadi. This is because the majority of rice fields in Lamongan district can also be used for fisheries. It is appropriate that the development of the agriculture and fisheries sectors receive special attention and the results can be seen as one of the keys to the success of the government in realizing people's welfare. The purpose of this study was to determine the descriptive data analysis of fish production in Lamongan district with the Friedman test. From the maximum value of production, the sector that is most superior in consumption fish production is pond cultivation, and the lowest is floating net cage cultivation. The districts with the most potential in consumption fish production are Glagah, Karamgbinangun and Turi Districts.